Inverted Ekphrasis and Hallucinating Stochastic Parrots: Deleuzean Insights into AI and Art in Daily Life (Itinera, 2025)
This study explores the potential of contemporary large language models (LLMs) to achieve Gilles Deleuze’s goal of integrating art into daily life. Deleuze’s philosophy, with its focus on creative repetition, finds a parallel in LLMs, which replicate and innovate artistic styles by transforming text prompts into various artistic expressions. Although LLMs can very effectively blend and mimic these styles, they remain mere tools – as suggested by the metaphor of a stochastic parrot; the true creative force remains the human artist. Currently, these models are experimental, and their artistic outputs, while impressive, are still viewed as pastiches rather than genuine art. Nonetheless, we can expect advances that may soon enable artists to use LLMs to create genuine artworks.